Characteristics and energy requirements of an alpha-aminoisobutyric acid transport system in Streptococcus lactis. - Thompson, J (1976)
Galactose-grown cells of Streptococcus lactis ML3 acculated alpha-aminoisobutyric acid (AIB) by using energy derived from glycolysis and arginine catabolism. The transport system displayed low-affinity Michaelis-Menten saturation kinetics. Using galactose or arginine as energy sources, similar V max and K m values for AIB entry were obtained, but on prolonged incubation the intracellular steady-state concentration of AIB in cells metabolizing arginine was only 65 to 70% that attained by glycolyzing cells. Efflux of AIB FROM PRELOADED CElls was temperature dependent and exhibited the characteristics of a first-order reaction. The rate of AIB exit was accelerated two- to threefold in the presence of metabolizable energy sources. Metabolic inhibitors including p-chloromercuribenzoate, dinitrophenol, azide, arsentate, and N, N'-dicyclohexylcarbodiimide either prevented or greatly reduced AIB uptake. Fluoride, iodoacetate and N-ethylmaleimide abolished galactose-dependent, but not arginine-energized, AIB uptake. K+ and Rb+ reduced the steady-state intracellular AIB concentration by approximately 40%, and these cations also induced rapid efflux of solute from actively transporting cells. Equivalent concentrations (10 mM) of Na+, Li+, or NH4+ were much less inhibitory. The proton-conducting ionophores tetrachlorosalicylanilide and carbonylcyanide m-chlorophenlyhydrazone abolished uptake and induced AIB efflux even though glycolysis and arginine catabolism continued at 60 and 140%, respectively, of control rates. A proton motive force is most likely involved in the active transport of AIB, whereas data from efflux studies suggest that energy is coupled to AIB exit in cells of S. lactis ML3.